Comparison of Serum Iron and Total Iron Binding Capacity Between Hemo and Peritoneal Dialysis Patients - B.H Ali; Z.I Al-Mashadani (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
In  this  study,  20  patients  were  selected    having  renal  failure  .10 patients  were  hemo&  10  peritoneal  dialysis  procedure. Patients  had been  given  r HuEPO    subcutaneous with supplement of Iron  dextran after  di alysis  . Hemoglobin  Hb  concentration Hematocrit(Hct),serum I ron ,total  Iron  binding  capacity,     transferrin  saturation percent  Ts%